Integrating Rahn And Takaful Contracts For Sharia Financial Protection: A Maqāṣid Al-Shari’ah Perspective - Choirunnisak Choirunnisak; Joko Setyono (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2026)
This study explores the integration of rahn and takaful contracts as a mechanism for strengthening Islamic financial protection from the perspective of Maqāṣid al-Sharī‘ah. Employing a qualitative library research approach, the study reviews and synthesizes relevant scholarly articles, books, and regulatory documents using thematic content analysis. The findings suggest that the integration of rahn and takaful creates a complementary system that combines financing access with risk protection. This integration enhances financial resilience and supports the realization of ḥifẓ al-māl (protection of wealth), one of the fundamental objectives of Maqāṣid al-Sharī‘ah. Based on the literature synthesis, the study proposes a Rahn–Takaful Integrated Protection Model that links financing, risk mitigation, and wealth preservation within a unified Islamic financial framework. The study contributes to the literature by offering a Maqāṣid al-Sharī‘ah-based conceptual framework for Islamic financial protection. However, the proposed model remains conceptual and requires empirical validation in different Islamic financial institutions and contexts.